KERJASAMA PEMERINTAH DAN SWASTA DI KOTA SURAKARTA (Studi Kerjasama Pemerintah dan Swasta di Surakarta 2005-2009) - PRIYATNO DKK, PRIYATNO DKK (Program Magister Ilmu Politik, Universitas Diponegoro, 2013)
The vast shifting map of local agencies makes it impossible to treat local governmentas a single organisation. The externalization of many services, the centralization of others,make local government is only one actor among a network of agencies in a modern-networksociety. Partnership between local government and private entities is seen as positive, evenessential. In Surakarta Municipality this kind of partnership is the result of a focus onoutcomes. Partnership is seen as a vehicle to create mutual trust as well as learning.Although the partnership In Surakarta municipality is still in it’s early stage, there have beenmany progress in innovation of development program, corporate focus, investment intraining and leadership development as well as cultural change. However, while progress isbeing made, the obstacle are still formidable.Key words: Governance, modern-network society, and Public-Private Partnership